Herpes Zoster Ophthalmicus in an 11-year-old Healthy Boy - Areeba Zaheer; Bithi Chowdhury; Aarushi Bhardwaj (Delhi Journal of Ophthalmology)
We report a rare case of an immunocompetent 11-year-old boy who presented with left-sided herpes zoster ophthalmicus with a negative Hutchinson sign. The child initially had a headache and pain in the forehead region, followed by a vesicular rash on the left side of the forehead and scalp. After 3 days of skin rash, he developed blurring of vision, conjunctivitis, and superficial punctate keratopathy. There was a history of having chicken pox at 4 years of age. He was treated with oral and topical acyclovir. The ocular pathology healed in 2 weeks and the skin lesions healed after 8 weeks with scarring.